Seloding Music Banyu Urip | Tabuh Seloding Banyu Urip - Dewa Gede Weda Astawa (GHURNITA: Jurnal Seni Karawitan, 2023)
This work entitled Banyu Urip raises a historical story of Beji Taman Sari, where Beji Taman Sari is a source of water that can provide healing to people affected by illness and also as a beji or purification of ida sesuhuan, which is realized in the form of a piece of Barungan gamelan Selonding with added distilled media. The purpose of using gamelan Seloding is to express the atmosphere of the procession of the Taman Sari Sangeh Village beji, which aims to introduce a broader meaning of the Sangeh Village Taman Sari beji which has sacredness and provides health for the people who paint the Beji Taman Sari in the Sangeh Village—in this work using several instruments including, one instrument penem petuduh (ugal), one nyong-nyong alit instrument, one nyong-nyong ageng instrument, one gong ageng instrument, one gong alit instrument, one kempul alit instrument, and one kempul ageng instrument. The stages or methods in question are eavesdropping (imitation), holding (refining), and ngelesin (smoothing). The stylist carries out the creative process from these stages or procedures by developing good patterns of structure playing techniques, which are generally gamelan.